2008
DOI: 10.1007/s11258-008-9540-9
|View full text |Cite
|
Sign up to set email alerts
|

Population genetics of an invasive riparian species, Impatiens glandulifera

Abstract: We assess the population genetic structure of the invasive riparian weed Impatiens glandulifera, and where possible, determine whether natural or anthropogenic dispersal best explains the observed patterns. Results are compared with a similar contemporary analysis for Heracleum mantegazzianum undertaken in the same catchments, and we suggest that some of the observed differences in genetic structure could be because of life history differences between these species. Our results confirm the importance of at lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(50 citation statements)
references
References 44 publications
4
46
0
Order By: Relevance
“…We discovered that deviations from HWE were frequent and inbreeding coefficients (F IS ) were high in individual populations and groups and among all samples from native or introduced regions (but slightly higher among the native plants), as expected in a plant with frequent self-pollination. Provan et al (2007) also found frequent significant deviations from HWE, while significant deviations were less frequent in the study by Walker et al (2009).…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…We discovered that deviations from HWE were frequent and inbreeding coefficients (F IS ) were high in individual populations and groups and among all samples from native or introduced regions (but slightly higher among the native plants), as expected in a plant with frequent self-pollination. Provan et al (2007) also found frequent significant deviations from HWE, while significant deviations were less frequent in the study by Walker et al (2009).…”
Section: Discussionmentioning
confidence: 60%
“…In a previous microsatellitebased study on I. glandulifera, Provan et al (2007) found in two introduced UK populations a total of 3.2 alleles per locus, while in the present study slightly higher numbers (mean 3.9) were detected in the UK. Conversely, Walker et al (2009) discovered very high allele numbers, 12.0 per microsatellite locus in a study that was based on three loci and included 13 UK populations. The mean expected heterozygosity detected by Provan et al (2007) was lower (0.384) than that reported in Walker et al (2009) (0.583) or in the UK material of the present study (0.543).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reviewed by Cross et al [17] and Dormontt et al [18], populations of various alien species might be distinguished by amplified fragment length polymorphism (AFLP) [19][20][21], by random amplified polymorphic DNA (RAPD) [22][23][24], by microsatellite/simple sequence repeat (SSR) [25][26][27][28][29] and by inter simple sequence repeat (ISSR) [24,30] loci. Among Balsaminaceae, the biggest variety of molecular markers, including nuclear microsatellites [25,31], chloroplast microsatellites [25] and RAPD [32] were applied to Impatiens glandulifera. Genetic variation among populations of native European Impatiens nolitangere was estimated by AFLP and ISSR markers [30].…”
Section: Introductionmentioning
confidence: 99%